AB0187 Long-term administration of fenspiride has no negative impact on bone mineral density and bone turnover in young growing rats. (15th June 2017) - Matuszewska, A; Nowak, B; Jędrzejuk, D; Landwόjtowicz, M; Bolanowski, M; Dziewiszek, W; Szelag, E; Zduniak, K; Kwiatkowska, J; Szeląg, A
Abstract : Background: In young organisms intensive bone turnover is observed and it allows the skeleton to achieve proper side, shape and weight of bones. It is extremely important to assess the influence on various drugs on growing bones. Fenspiride is registered for therapy of acute and chronic respiratory tract infections in children and adolescence. It decreases the synthesis of proinflammatory cytokines, blocks H1 receptors and has bronchodilatotory properties. Objectives: The aim of the study was to assess the influence of long-term administration of fenspiride on bone mineral density and selected markers on bone turnover in young growing rats. Methods: The experiment was carried out on18 young (8-week-old) male Wistar rats receiving standard diet containing 1.2% of calcium ans 0.7% of phosphate. Rats were randomly assigned to one of two groups (9 animals in each group): group F – rats receiving fespiride (15 mg /kg) in saline solution (4ml/kg), and group C (control group) - rats receiving saline solution (4ml/kg). Saline solution and fenspiride were given intragastrically once daily for 90 days (from day 3 to day 92). On day 1 and 93 blood samples for serum isolation were collected. Markers of bone turnover were assessed with commercial ELISA kits according to producers' instruction. Bone mineral density (BMD) was measured by dual-energy X-ray absorptiometry (DXA) with Hologic DXA equipment (Hologic Dicovery W 81507) using a small animal software. The experiment was performed with the approval of the First Local Ethics Committee for Experiments on Animals in Wroclaw. Results: On Day 1 there was no difference in age and body weight between groups. On Day 1 no difference in total body bone mineral density (BMD) (0.160±0.0065 g/cm 2 vs. 0.1608±0.0056 g/cm 2 ), lower limbs BMD (0.232±0.0267 g/cm 2 vs. 0.2274±0.0314 g/cm 2 ), serum levels of bone turnover markers (osteocalcin: 1000.921±109.0705 pg/ml vs. 952.5777±178.5306 pg/ml; bCTX: 280.089±54.4298 pg/ml vs. 292.8979±116.0042 pg/ml; osteoprotegerin: 3.5±0.6338 pg/ml vs. 3.7963±0.6894 pg/ml; RANKL: 0.167±0.4099 pg/ml vs. 1.0218±1.2717 pg/ml) was detected. On Day 93 there was no difference in body weight, total body BMD and lower limbs (0.212±0.0104 g/cm 2 vs. 0.2035±0.0242 g/cm 2 ; 0.264±0.0159 g/cm 2 vs. 0.2520±0.0271 g/cm 2, respectivelly) between groups. On Day 93 no difference between groups in serum bone turnover markes was detected (OC: 422.758±92.3316 pg/ml vs. 429.2071±83.0520 pg/ml; bCTX: 307.748±77.6733 pg/ml vs. 285.3486±79.16334; OPG: 5.466±0.7815 pg/ml vs. 5.3520±1.6458 pg/ml; RANKL:0.647±0.8457 pg/ml vs. 0.5630±0.8608 pg/ml). Conclusions: Long-term administration of fenspiride has no negative impact on bone mineral density and bone turnover in young growing rats Acknowledgements: Research was supported with Wroclaw Medical University Grant for Young Researchers Pbmn 138. Disclosure of Interest: None declared